Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
Hence a = 3.66 and -3.628
b = 0.834 and -2.634
Step-by-step explanation:
Given the equations
a-2b =2 -------- (1)
a²+b²+2a -3b =19 --------(2).
From 1;
a = 2 + 2b
Substitute into 2
(2+2b)²+b²+2a -3b =19
Expand
4 + 8b + 4b²+b²+2(2+2b)-3b = 19
4b²+b²+8b+4b+4+4-3b = 19
5b²+9b+8 = 19
5b²+9b-11 = 0
b = -9±√81+4(55)/2(5)
b= -9±√301/10
b = -9+17.34/10 and -9-17.34/10
b = 8.34/10 and -26.34/10
b = 0.834 and -2.634
Since a = 2+2b
a = 2+2(0.834)
a= 2 +1.668
a = 3.668
Also
a = 2+2(-2.634)
a = 2 - 5.628
a = -3.628
Hence a = 3.66 and -3.628
b = 0.834 and -2.634
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.